Gaiola vs Borbone system: a comparison between 18th Century anti-seismic case studies - Stellacci, S.; Ruggieri, N.; Rato, V. (International Journal of Architectural Heritage, 2016)
This article briefly discusses the seismic-resistant heritage of the 18th century, circumscribed in Lisbon's Baixa Pombalina (post 1755) and case baraccate of Southern Italy (post 1783).A comparison of these anti-seismic systems is discussed through the architectural principles and the mechanical behavior. It is shown that, despite the wide diversity of cases and the different geo-historical conditioning, both systems arise from an intuition of the compound seismic efficiency, the typical pragmatism of the enlightenment period and an interpretation of the classic composition code.Two specific case studies, a private building in Baixa Pombalina (Lisbon) and the Bishop's Palace of Mileto (Calabria region) are compared. We briefly analyze: (i) configuration and structural principles; (ii) characteristics of the materials; and (iii) seismic behavior.A standardized spatial morphology closely linked to traditional construction techniques positively determines the seismic response and it is one of the key common factors in this heritage to be preserved.In both cases, the architectural and structural choices are crucial to the seismic response of the building and must be respected as an identity of a specific technical knowledge. Moreover, this materiality represents a historical continuity of the community's memory that requires transdisciplinary, critical understanding, and preservation.